Childhood Obesity as a Global Problem: a Cross-sectional Survey on Global Awareness and National Program Implementation - Aman B. Pulungan; Helena A. Puteri; Amajida F. Ratnasari; Hilary Hoey; Agustini Utari; Feyza Darendeliler; Basim Al-Zoubi; Dipesalema Joel; Arunas Valiulis; Jorge Cabana; Enver Hasanoğlu; Naveen Thacker; et al. (Galenos Yayincilik, 2024)
INTRODUCTION: The rising global epidemic of childhood obesity is a major public health challenge. Despite the urgency, there is a lack of data on the awareness and implementation of preventative measures. The aim of this study was to identify areas for improvement in the prevention and management of childhood obesity worldwide. METHODS: A cross-sectional electronic survey was distributed to 132 members of national pediatric societies of the International Pediatric Association. RESULTS: Twenty-eight (21.2%) participants, each from a different country across six World Health Organization (WHO) regions completed the survey. Most participants reported that national prevalence data of childhood obesity is available (78.6%), and the number increased during the Coronavirus disease-2019 pandemic (60.7%). In most countries (78.6%), the amount of sugar and salt in children's products is provided but only 42.9% enacted regulations on children-targeted advertising. Childhood obesity prevention programs from the government (64.3%) and schools (53.6%) are available with existing support from private or non-profit organizations (71.4%). Participants were aware of WHO's guidance concerning childhood obesity (78.6%), while fewer were aware of The United Nations International Children's Emergency Fund's (UNICEF) guidance (50%). Participants reported that WHO/UNICEF guidance acted as a reference to develop policies, regulations and national programs. However, progress was hindered by poor compliance. Lastly, participants provided suggestions on tackling obesity, with responses ranging from developing and reinforcing policies, involvement of schools, and prevention across all life stages. DISCUSSION AND CONCLUSION: There are different practices in implementing prevention measures to counter childhood obesity globally, particularly in statutory regulation on food advertising and national programs. While support and awareness was relatively high, implementation was hindered. This reflects the need for prompt, country-specific evaluation and interventions.